Some Properties of a Reaction Mechanism Analogous to Thrombin Formation - Surgenor, Douglas Mac N (Thrombosis and Haemostasis, 1959)
Using an analog computor, the behavior with respect to time of a model chemical reaction mechanism has been studied. This mechanism consists of a consecutive series of reactions, the product of which corresponds to a prothrombin activator that acts enzymatically upon prothrombin. The striking resemblance in behavior between the model mechanism and the natural system strengthens current concepts of prothrombin activator formation.